Climate change biology - Hannah, Lee Jay (Elsevier, Academic Press, an Imprint of Elsevier, 2022)
Climate Change Biology, Third Edition, addresses how climate change may affect life on the planet, particularly its impact on biology. Presented in three parts, it deals extensively with the physical evidence of climate change and modeling efforts to predict its future. Biological responses are then addressed, from individual physiology, to populations and ecosystems, adaptation and evolution. The final section examines the specific impact climate change may have on natural resources, particularly relating to human livelihood. This book will be a useful asset to the growing number of both undergraduate and graduate courses on climate change. All sections are updated using the more than 5,000 research papers that have appeared on the topic since the publication of the second edition. Sections on the combined effects of ocean acidification and climate change are especially strengthened, with over six new case studies and end of chapter questions in each chapter.